Analisis Pengaruh Tingkat Kepuasan Kerja Terhadap Kinerja Karyawan yang Dimoderasi oleh Motivasi (Studi Kasus di Hotel Cihampelas 2, Bandung) - Gozaly, Jimmy; Anatasia, Novita (Zenit, 2012)
This study was conducted in the Cihampelas Hotel 2 Bandung, which has propose to minimize the level of employee’s absence and to improve the service level of Cihampelas Hotel 2 by knowing the level of job satisfaction which is owned by Cihampelas Hotel 2’s employee, employee’s job motivation, and influence both of that towards employee’s job performance. The study variables such as job satisfaction as independent variable, job performance as dependent variable, and job motivation as moderat variable. Census sampling was used in this study because all of Cihampelas Hotel 2’s employee at low management amounting to 25 employee became respondents in this study. Based on the processing by descriptive statistics and by multiple linear regression, the result showed that 13 sub variables influented employee’s job performance. The correlation value for all sub variables was 92,3% and the determination coefficients was 85,1%.  Some proposals that could be prioritized by Cihampelas Hotel 2 such as the company may appreciate the employee’s work, company should determine the break time carefully, company can give the warning to employee that are less effective at work, and company may give the opportunity and the trustworthy to employee to work independently.  Keywords:  Job satisfaction, job motivation, job performance, multiple linear regression